Motivational Processes Influencing Mental Health Among Winter Sports Athletes in China - Wu, Xinran; Zainal Abidin, Nor Eeza; Aga Mohd Jaladin, Rafidah (Frontiers in Psychology, 2021)
This study examined the association between motivational processes, psychological distress (depression, anxiety, and stress), and burnout among winter sports athletes within the Hierarchical Model of Intrinsic and Extrinsic Motivation (HMIEM). A total of 685 winter sport athletes participated in this study (377 males, 308 females, age range 18-25 years), from three sport universities across nine winter sports. They completed five psychometric inventories related to motivational factors and mental disorders. Overall, a task-involving climate was shown to enhance athletes’ autonomous motivation and controlled motivation through basic psychological need satisfaction, thereby reducing the incidence and prevalence of psychological distress and burnout among winter sport athletes. In contrast, a high ego-involving climate was shown to lead to a decrease in basic psychological need satisfaction, eliciting a pathway to amotivation, and thus improving the incidence and prevalence of psychological distress and burnout. These findings showed the complex relationships between various motivational factors and mental health disorders among winter sport athletes and supports the essential requirement for adding mental health factors to the outcomes of the HMIEM sequence.